Legal Review Regarding the Application of Criminal Sanctions for Acts of Defamation Through Social Media - Mukminah, Lily Solichul (Metromedia, 2024)
This research examines the impact of imposing criminal sanctions on defamation through social media on society at large. Using a normative juridical research method, analysis is conducted on relevant legal regulations and the elements involved in defamation. The study highlights the importance of imposing criminal sanctions as an instrument to uphold justice, prevent similar actions in the future, and consider the psychological and social impacts on victims and perpetrators. By understanding the deterrence effect of criminal sanctions and evaluating their effectiveness, this research contributes to a comprehensive understanding of the role of legal enforcement in addressing defamation issues in the digital era. It provides insights into the complexities of defamation cases in the online realm and underscores the significance of legal measures in safeguarding individual rights and maintaining societal integrity in the face of evolving digital communication platforms.